2012
DOI: 10.1177/0003122412450573
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Deterrence

Abstract: Rational choice approaches have long suggested that reducing unwanted behavior requires raising the costs (or perceived costs) of a behavior through the threat of punishment-a process commonly referred to as deterrence. In the eighteenth century, Beccaria ([1764] 1983) argued that the state should punish law-breakers just enough so that the burdens of punishment outweigh any pleasure derived from perpetrating the crime-an idea that directly informs U.S. criminal law, military strategy, and a host of other soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(26 citation statements)
references
References 88 publications
1
25
0
Order By: Relevance
“…Given that lags in some of the defiance effects discussed in this book are much longer than those measured by Carson (2017)-for example, jihadist imaginary effects of US state criminality and increased recruitment to jihadist madrassas turning out active jihadists years later-we should emphasise that part of Carson's conclusions that suggest this is an unwise policy because most of the targeted killings 'either had no influence or were associated with a backlash effect ' (p. 191). Carson's results are consistent with those of Dugan and Chenoweth (2012) on targeted extrajudicial assassinations of Palestinians. Chapter 9 concluded that, up to 2003, or perhaps 2005, deterrence effects on the Taliban exceeded defiance effects, but, after 2005, Taliban defiance clearly exceeded deterrence.…”
supporting
confidence: 77%
“…Given that lags in some of the defiance effects discussed in this book are much longer than those measured by Carson (2017)-for example, jihadist imaginary effects of US state criminality and increased recruitment to jihadist madrassas turning out active jihadists years later-we should emphasise that part of Carson's conclusions that suggest this is an unwise policy because most of the targeted killings 'either had no influence or were associated with a backlash effect ' (p. 191). Carson's results are consistent with those of Dugan and Chenoweth (2012) on targeted extrajudicial assassinations of Palestinians. Chapter 9 concluded that, up to 2003, or perhaps 2005, deterrence effects on the Taliban exceeded defiance effects, but, after 2005, Taliban defiance clearly exceeded deterrence.…”
supporting
confidence: 77%
“…The political violence (e.g., Downes 2007; Kalyvas and Kocher 2007; Lyall 2009) and state repression (e.g., Daxecker and Hess 2013; Dugan and Chenoweth 2012; Hafez 2003; Mason and Krane 1989; Rasler 1996) literatures have paid substantial attention—though with mixed findings—to the effects of different types of targeting and repression. However, it is crucial to note that for these studies the main outcome of interest is the intensity of violence and contention in the short run, during the same violence/repression campaign.…”
Section: Repression Resistance Skillsmentioning
confidence: 99%
“…This article also argues that the toolkit is learned and that an important pathway to its acquisition is through exposure to repression. Extensive research on political violence and contentious politics focuses on the short-term effects of repression; for example, whether it facilitates or impedes mobilization during the same episode of contention (Downes 2007; Dugan and Chenoweth 2012; Kalyvas and Kocher 2007; Lyall 2009; Mason and Krane 1989). Exposure to repression and violence, however, also has long-term effects (Blattman 2009; Daly 2012; Jha and Wilkinson 2012).…”
mentioning
confidence: 99%
“…Other researchers, however, distinguish the predictability of Israeli actions and the limited predictability of Palestinian actions (Hafez and Hatfield 2006;Jaeger and Paserman 2006. Two recent analyses find periods of greater predictability alternating with periods of lesser predictability (Dugan and Chenoweth 2012;Golan and Rosenblatt 2011). Golan and Rosenblatt (2011) suggest that it is "implausible" to assume a single impulseresponse function for a phenomenon that bridges multiple "epochs," and they call for further data gathering on additional "aspects of this multifaceted conflict."…”
Section: Israel-palestinementioning
confidence: 99%